A decision support framework for identifying novel ideas in new product development from cross-domain analysis. (September 2017) - Mirtalaie, Monireh Alsadat; Hussain, Omar Khadeer; Chang, Elizabeth; Hussain, Farookh Khadeer
Highlights: A systematic framework, not only to satisfy the current customers' needs by introducing minor innovations but also to generate ideas that assist organizations to capture new customers, is proposed. The proposed data centric framework utilises additional information relating to products from either far-field or related domains to generate new ideas in the ideation phase of NPD. A thorough literature review of ideation from cross-domain products is presented and the need for a systemized framework is highlighted. Our proposed framework, FEATURE, comprising three modules, is then explained. The first module, namely the New Feature Finder, is discussed in detail, along with the experimental results to demonstrate and validate the novel ideas it proposes. Abstract: In current competitive times, product manufacturers need not only to retain their existing customer base, but also to increase their market share. One way they can achieve this is by generating new ideas and developing novel products with new features. As highlighted in the literature, in generating new ideas to develop novel and innovative products, it is important that product designers satisfy the needs of both current customers and new customers. However, despite the large number of existing studies that identify novel features in the ideation phase, product designers do not have a systematic framework that utilises additional information relating to products from either far-field or related domains to generate such new ideas in the ideation phase. This paper presents our proposed framework FEATURE which provides just such a systemic framework for product designers in the ideation phase of new product development. FEATURE has three phases. The first phase identifies and recommends to the product designers novel features that can be added to the next version of a reference product. In order to incorporate the customer's voice into the ideation phase, the second phase ascertains the popularity of the proposed features by using social media. The third phase ranks the proposed features based on the designer's decision criteria to select those that should be considered further in the next phases of new product development. We explain the importance of each phase of FEATURE and show the working of its first module in detail.